Efforts of the Sabhara Patrol Unit in Increasing Two-Wheel Theft Defense - Sudding, Ananda Praditya (Police Studies Review, 2024)
This research was motivated by the rise of criminal acts of theft in the jurisdiction of the Sumedang Police, which was linked to efforts to improve the performance of the Sabhara Unit patrol unit in preventing crimes occurring in the jurisdiction of the Sumedang Police. This research aims to determine the description of the occurrence of two-wheeled theft (R2) in the jurisdiction of the Sumedang Police, the implementation of patrols by the Sumedang Police Sabhara Unit patrol unit in preventing the occurrence of criminal acts of two-wheeled theft (R2), as well as the factors that influence the patrol unit’s efforts. This research was carried out with a qualitative approach, using field research methods, as well as data collection techniques using interviews, observations and document review. To discuss the problem the author uses conceptual literature, namely the Sabhara concept, patrol concept, management theory (George R. Terry), and performance theory (Amstrong and Baron). The existing data was then analyzed using data analysis techniques, namely data reduction, data presentation and drawing conclusions. The research results show that the preventive actions carried out by the Sabhara Unit through patrols have been running but are not optimal due to factors that hinder the performance of the patrol unit, including the quantity and quality of personnel, facilities and infrastructure, methods of implementing patrols, and leadership supervision. Efforts are needed to improve the performance of the Sumedang Police Sabhara Unit patrol unit by increasing the quantity and quality of personnel, supporting facilities and infrastructure, good implementation methods and increasing supervision of patrol implementation.